Availability and Pricing of Infant Snack Foods in Low-Income Communities Across Rhode Island. (29th May 2020) - Moore, Amy; Vadiveloo, Maya; McCurdy, Karen; Tovar, Alison
Abstract: Objectives: Marketing for infant snack foods has increased in the past 20 years, yet little is known about the availability and pricing of these foods. This study assessed the availability and pricing of infant snack foods in grocery stores in low-income communities across Rhode Island. Methods: A random sample of grocery stores (N = 20) was selected from low-income census tracts. Twelve items were developed for this study to assess the availability and pricing of infant foods (e.g., infant formula, purees) and infant snack foods (e.g., puffs, melts). The Nutrition Environment Measures Survey in Stores (NEMS-S) was used to assess the nutrition environment including the availability, pricing, and quality of healthful foods compared to less healthful foods. Total NEMS-S scores range from -9 to 54 with higher scores indicating more healthful foods. Data were collected by trained research assistants during a 2-week period to limit confounding due to restocking and seasonality. This analysis included descriptive statistics to summarize the infant snack foods and the total nutrition environment. Results: All 20 grocery stores in this sample sold infant foods and 18 stores sold infant snack foods. Availability of infant snack foods varied by store with puffs having the highest availability (n = 18) followed by melts (n = 15), teething cookies (n = 10), and baby yogurt (n = 7). Baby yogurt had the highest average price per serving (0.72) followed by melts (0.62), teething cookies (0.50), and puffs (0.49). Mean total NEMS-S score for all grocery stores was 27.5 ( SD = 4.7). Conclusions: Infant snack foods are available in grocery stores in low-income communities. Recent increases in marketing and availability of infant snack foods make it important to explore factors that influence caregivers to offer these snacks. Future studies should explore these factors and develop evidence-based recommendations for developmentally appropriate, healthful snacking during infancy. Funding Sources: This work was supported by the USDA National Institute of Food and Agriculture, [Hatch/Tovar/1, 001, 894].